EARLY SKIN AGEING -PREVENTION AND MANAGEMENT THROUGH - Dr. Shubha Kaushal, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2024)
This article delves into the   impact of ageing on skin. Light is put on the predisposing factors that result in early ageing signs, the physiological changes on ageing skin. The  various possibilities through ayurvedic approach to deal with prevention of early skin ageing and its management through herbal intervention are the key features covered in this article.